Defining the dermoscopic characteristics of fast-growing cutaneous melanomas. Issue 3 (June 2015) - Tejera-Vaquerizo, Antonio; Arias-Santiago, Salvador; Nagore, Eduardo; Martín-Cuevas, Paula; Orgaz-Molina, Javier; Traves, Victor; Herrera-Acosta, Enrique; Naranjo-Sintes, Ramón; Guillén, Carlos; Herrera-Ceballos, Enrique
Abstract : A high growth rate in melanomas has been associated with a more aggressive phenotype and worse survival. The aim of this study was to define the dermoscopic characteristics associated with this type of cutaneous melanoma. We carried out a retrospective study of 132 cutaneous melanomas, analyzing certain clinical characteristics and the most important dermoscopic variables related to the melanomas. Fast-growing melanomas were considered to be those with a growth rate of more than 0.5 mm per month. Fast-growing melanomas more often lacked an atypical network, were symmetrical, presented ulceration, and were hypopigmented. The dermoscopic vascular pattern often showed atypical irregular vessels and milky-red areas. The association of these two is a specific characteristic. Fast-growing melanomas have a characteristic phenotype and dermoscopy can be useful for their identification.